The Authority of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency in the Legal Protection of Land Rights Holders whose Transfer of Rights is Revoked - Ni Wayan Ari Susanti; Nurianto RS; Siti Nurmawan Damanik (CV. Syntax Corporation Indonesia, 2024)
Disputes over the transfer of land ownership rights through sales often arise in the community due to Indonesia's land registration system, which follows a negative system. This system allows for multiple legal defects in registered land rights certificates, potentially leading to cancellation requests. This research addresses two main issues: the authority of the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) in handling land cases and the form of legal protection for land rights holders whose transfers are cancelled. This normative legal research employs a statutory and case approach, using document studies for data collection and analyzing the data through descriptive methods and legal analogies (argumentum per analogy). The study concludes that the ATR/BPN's authority in handling land cases is outlined in Permen ATR/BPN No. 21 of 2020. The agency offers two alternatives for resolving disputes: judicial settlement for court decisions and mediation for a win-win solution and peace agreement. Additionally, legal protection for land rights holders, particularly third parties with certificates cancelled due to administrative defects, can be provided both preventively and repressively to ensure legal certainty and protection for all parties involved.